Best economical quantity of nitrogen used on pangola grass and its determination by the factor’s actual relative price - Salles, Pedro Afonso Almeida de; Gonçalves, José Otávio Neto (Pesquisa Agropecuaria Brasileira, 2014)
The economic analysis of the effect of nitrogen used on pangola grass (Digitaria decumbens Stent) pasture was done. In the first period, the response curve was estimated based on a field experiment conducted during four years, in which this grass was submitted to five different levels of nitrogen (0, 100, 200, 300, 400 kg/ha of N). The equation selected by regression was a polynomial of second degree: Y = 2289.23 + 52.45 N - 0.0784 N2 , where Y is the production in kg/ha and N is the quantity of N in kg/ha. In the second period, the results of the economic analysis showed that the meat producer reaches the highest economical efficiency in October of 1981, with 157 kg/ha/year of N. The milk producer reaches it with 249 kg/ha/year. The highest technical efficiency was reached with 333 kg/ha/year of N. Searching for an up-to-date analysis, the nitrogen levels were determined to reach the highest economical efficiency, at any price, of this production factor, related with the cattle breeding products (meat and milk), since that it is up to the producer to decide between the alternatives, which Is the most practicable in its conditions and prices.